2019
DOI: 10.5005/jp-journals-10054-0104
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia: Postpartum Resolution of Hypertension, Proteinuria and Serum N-terminal B-type Natriuretic Peptide

Abstract: Background: Postpartum persistent proteinuria and hypertension (HT) is associated with development of chronic kidney disease and cardiovascular disease in later life. AIMS & OBJECTIVES: To evaluate blood pressure, proteinuria and serum NT-pro-BNP in proteinuric preeclamptic (PE) women and study their postpartum resolution till 3 months and determine the associated risk factors. Material and methods: 100 PE women enrolled included 66 women with mild (group A) and 34 with severe PE (group B). BP, urinary protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…22,25 High levels of serum creatinine were associated with persisting hypertension at twelve weeks postpartum among preeclampsia patients (aRR=1.35, 95% CI:1.241-3.606, p=0.032) at this hospital. This result was consistent with the one of Ndayambagye et al 4 in Mulago hospital in Uganda, Saini et al in India 26 as well as that by Babah et al 21 in Nigeria. Because raised serum creatinine is a known marker for chronic renal disease, it is possible that the women who had elevated serum creatinine had underlying kidney injury resulting from either the preeclampsia itself, or probably were previously undiagnosed asymptomatic patients of kidney disease, which per se is an independent predictor of the development and progression of persisting hypertension and its associated morbidity and mortality.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…22,25 High levels of serum creatinine were associated with persisting hypertension at twelve weeks postpartum among preeclampsia patients (aRR=1.35, 95% CI:1.241-3.606, p=0.032) at this hospital. This result was consistent with the one of Ndayambagye et al 4 in Mulago hospital in Uganda, Saini et al in India 26 as well as that by Babah et al 21 in Nigeria. Because raised serum creatinine is a known marker for chronic renal disease, it is possible that the women who had elevated serum creatinine had underlying kidney injury resulting from either the preeclampsia itself, or probably were previously undiagnosed asymptomatic patients of kidney disease, which per se is an independent predictor of the development and progression of persisting hypertension and its associated morbidity and mortality.…”
Section: Discussionsupporting
confidence: 91%
“…The greater frequency of persisting hypertension in women aged 35 years and more has also been recently hypothesized to result in increased release of angiogenic factors and abnormal placentation thus increasing susceptibility to severe preeclampsia and its sequelae such as persisting hypertension. Indeed, study results of Saini et al 26 and Levine et al 20 revealed that severe preeclampsia was an independent predictor of persisting hypertension postpartum. And the reverse is reportedly true for women with persisting hypertension.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the C HPXPS of 1000 cycled TNO700 electrode in Figure 4d, the peaks at 287.8 and 286.2 eV are assigned to C=O group and C-OH and C-O-C groups, [62,63] which are due the decomposition of carbonates during the cycling. Those aforementioned groups is also apparent on the O HRXPS of the 1000 cycled electrode, [13,[64][65][66] revealing the decomposition of carbonates. Additionally, the presence of LiF peak at 686.1 eV on the F HRXPS can be attributed to the side reaction of LiPF 6 salt.…”
mentioning
confidence: 88%
“…According to Unverdi S et al (Gupta et al, 2019), postpartum hypertension should be evaluated concerning sustained proteinuria, persistent hematuria, or impaired renal function. A percutaneous kidney biopsy should be performed on women with positive signs of kidney disease.…”
Section: Discussionmentioning
confidence: 99%